PENERAPAN KEBIJAKAN TAMBAHAN PENGHASILAN DI DALAM MENINGKATKAN KEPUASAN PEGAWAI DI KANTOR KECAMATAN BONTANG - Hartoni .; Anthonius Margono; Anwar Alaydrus (Jurnal Administrative Reform, 2017)
The purpose of this study to describe and analyze the implementation of additional measures to improve the income of employee satisfaction at the District Office West Bontang and analyze the factors that support and hinder. This study is descriptive with qualitative approach. Data was obtained through interviews, observation and documents, then the data were analyzed using an interactive model. Results of the study revealed that the implementation of additional policies in order to increase the income of employee satisfaction at the District Office West Bontang already performing quite well.